(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Banking, being an important part of economic development, plays a different role in different countries. Uzbekistan and China, as two important emerging economies, have certain similarities and differences in the development of banking system. As an important part of the Asian economic system, the banking systems of Uzbekistan and China are of great importance in understanding the economic development and financial markets of these two countries. This paper analyses a number of aspects to identify their similarities and differences, analyses the differences between the banking sectors of the two countries in terms of financial innovation, market competition, risk management, etc., and finally puts forward suggestions to promote the development of Uzbekistan’s banking sector.